Autonomous motivation is associated with the maintenance stage of behaviour change in people with affective disorders. (30th June 2016) - Vancampfort, Davy; Moens, Herman; Madou, Tomas; De Backer, Tanja; Vallons, Veerle; Bruyninx, Peter; Vanheuverzwijn, Sarah; Mota, Cindy Teixeira; Soundy, Andy; Probst, Michel
Abstract: The present study examined whether in people with affective disorders motives for adopting and maintaining physical activity recommendations (as formulated by the self-determination theory) differed across the stages of behaviour change (identified by the transtheoretical model). A total of 165 (105♀) persons (45.6±14.2years) with affective disorders [major depressive disorder (n=96) or bipolar disorder (n=69)] completed the Behavioural Regulation in Exercise Questionnaire-2 and the Patient-centred Assessment and Counselling for Exercise questionnaire. Discriminant and multivariate analyses demonstrated that persons with affective disorders at the early stages of change have less autonomous and more controlled physical activity motives than those at the later stages. Our results suggest that autonomous motivation may have an important role to play in the maintenance of health recommendations in persons with affective disorders. Longitudinal and intervention studies should be designed in people with affective disorders to identify the causal pathways between motives for maintaining health recommendations, effective changes in health behaviour and physical and mental health outcomes. Highlights: Persons with affective disorder who maintain their physical activity behaviour are in particular autonomously motivated. Feelings of being ashamed or guilty and low self-efficacy do characterize only those initiating physical activity.